2009
DOI: 10.1210/en.2008-0541
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of Steroidogenic Acute Regulatory Protein in the Rodent Ovary and Placenta: Alternative Modes of Cyclic Adenosine 3′, 5′-Monophosphate Dependent and Independent Regulation

Abstract: Steroid hormone synthesis is a vital function of the adrenal cortex, serves a critical role in gonadal function, and maintains pregnancy if normally executed in the placenta. The substrate for the synthesis of all steroid hormones is cholesterol, and its conversion to the first steroid, pregnenolone, by the cholesterol side-chain cleavage cytochrome P450 (CYP11A1) enzyme complex takes place in the inner mitochondrial membranes. Steroidogenic acute regulatory protein (STAR) facilitates the rate-limiting transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 63 publications
(81 reference statements)
0
52
1
Order By: Relevance
“…To obtain molecular insight into these mechanisms, the functional involvement of CREB and c-Jun/c-Fos in PKD signaling was assessed, because these transcription factors have been demonstrated to be instrumental in StAR gene transcription (23,28). MA-10 cells were transfected with either 100 nM of a negative control siRNA or 50 nM of two PKD (100 nM total) specific siRNAs (Fig.…”
Section: Pkd Signaling Involves Creb-and C-jun/c-fos-mediated Transcrmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain molecular insight into these mechanisms, the functional involvement of CREB and c-Jun/c-Fos in PKD signaling was assessed, because these transcription factors have been demonstrated to be instrumental in StAR gene transcription (23,28). MA-10 cells were transfected with either 100 nM of a negative control siRNA or 50 nM of two PKD (100 nM total) specific siRNAs (Fig.…”
Section: Pkd Signaling Involves Creb-and C-jun/c-fos-mediated Transcrmentioning
confidence: 99%
“…Noteworthy, whereas PKC-mediated induction of steroid synthesis is remarkably low compared with PKA signaling, it modulates gonadotropin and/or cAMP/PKA-stimulated steroidogenic responsiveness (24 -26) and thus may play important roles in various adrenal and gonadal steroidogenic functions. Transcription of the StAR gene is influenced by multiple DNA regulatory elements, including cAMP response-element (CRE)-binding protein (CREB)/CRE modulator and activator protein-1 (AP-1, Fos/Jun) (18,23,27,28). CREB-binding protein (CBP) and its functional homolog, p300, are transcriptional coactivators, which interact with a variety of transcription factors and thus play critical roles in gene regulation (23,29).…”
mentioning
confidence: 99%
“…The rate-limiting step in steroidogenesis is the transport of cholesterol from the outer to the inner mitochondrial membrane, where it is converted to pregnenolone by cytochrome P450 cholesterol side chain cleavage complex. STAR, a mitochondrial phosphoprotein, has been identified as the critical cholesterol transport protein (14,75) and has been extensively studied across numerous species (10,83,85). In bovine follicles, the expression of STAR is restricted to the theca interna (3,73); however, it is acquired in granulosa cells following luteinization (3,61).…”
Section: Discussionmentioning
confidence: 99%
“…In steroidogenic cells, C/EBPα and C/EBPβ isoforms are detected and C/EBPβ expression is increased by cAMP-mediated mechanisms in mouse testicular Leydig and ovarian granulosa cells [136][137][138]. The functional C/EBP element in the StAR promoter is highly conserved and C/EBPβ in MA-10 Leydig cell, rodent granulosa-luteal cell, and human granulosa-luteal cell nuclear extracts was shown to bind to the mouse and human StAR proximal promoter [139][140][141]. Protein-protein interactions between C/EBPβ and SF-1 and C/ EBPβ and GATA-4 have been proposed to contribute to Leydig and granulosa cell StAR gene expression, respectively.…”
Section: Bzip Transcription Factors Involved In Camp-dependent Star Gmentioning
confidence: 99%
“…StAR expression and steroid production are important during both phases and StAR gene regulation switches from a cAMP-dependent to a cAMP-independent mechanism. The switch is mediated by an AP-1 family member replacing CREB at the CRE/AP-1 element and recruitment of C/EBPβ to its functional element upstream of the CRE/AP-1 site [141]. ChIP analysis using mouse granulosa-luteal cells showed that C/EBPβ was recruited to the StAR promoter with no apparent increase in CREB/CREM association, indicating a tissue-specific difference in StAR regulation.…”
Section: Model For Camp-pka-dependent Activation Of Star Transcriptionmentioning
confidence: 99%